Impact of organizational characteristics on employees’ entrepreneurial orientation with mediating role of knowledge process capabilities and moderating role of psychological factors in the era of COVID-19 - Basheer, Muhammad Farhan; Sabir, Saeed Ahmad; Raoof, Rabeeya; Hameed, Waseem Ul; Jabeen, Saida (Frontiers in Psychology, 2022)
Purpose The study aims to investigate the impact of organizational characteristics and knowledge process capabilities on the entrepreneurial orientation among the manufacturing industry employees in the Punjab province of Pakistan. Additionally, this study has examined the mediating role of knowledge process capabilities in the relationship between organizational characteristics and entrepreneurial orientation among those employees and the moderating effect of psychological factors on the relationship between organizational characteristics and entrepreneurial orientation. Design, methodology, and approach The study has employed the survey-based methodology and data are collected with the aid of self-administered questionnaires. This study utilized the partial least squares structural equation modeling (PLS-SEM) to establish the validity and reliability of the measurement model and test the relationships. The response rate of the current study is 64.66%. Findings The study findings have shown mixed results as one of the organizational characteristics, namely, resource and time availability is an insignificant determinate of entrepreneurial orientation among the manufacturing industry employees in Punjab province of Pakistan. Whereas management support, rewards, work discretion, and knowledge process capabilities appear as significant determinates of employees’ entrepreneurial orientation. The results indicated that knowledge process capabilities have a mediating role in the relationship between organizational characteristics and employees’ entrepreneurial orientation. Moreover, psychological factors, namely, propensity to take risk and locus of control have a significant moderating role on the relationship of management support, rewards, and work discretion with employees’ entrepreneurial orientation. Practical implications The empirical insights on the study are valuable for policymakers and managers in manufacturing sectors of developing countries, such as Pakistan, to enrich their work performance through the understanding impact of organizational characteristics and knowledge process capabilities on the entrepreneurial orientation with moderating role of psychological factors. Originality and value Studies on the mediating impact of knowledge process capabilities on the linkage between organizational characteristics and entrepreneurial orientation with the moderating role of psychological factors remain limited. This study is one of the earliest studies that investigate these inter-relationships.